The Effect of Metacognitive Questioning Instruction Performed in Cooperative Learning Environments on the Mathematical Problem Solving Skills of 4th Grade Primary School Students - Mehmet Koray SERİN and İsa KORKMAZ (Elementary Education Online, 2023)
The aim of this study is to examine the effect of metacognitive questioning instruction practices performed in cooperative learning environments on the mathematical problem solving skills of 4th grade primary school students. The study was planned according to comparison group pre-test post-test quasiexperimental study design. The participants of the research included 94 students studying at the 4th grade of a state primary school in Kastamonu province in 2013-2014 academic year. The courses in treatment group-1 (n=33) were based on metacognitive questioning instruction practices performed in cooperative learning environments and the courses in treatment group-2 (n=31) were carried out based on cooperative learning method without the support of metacognitive strategies. On the other hand, in the control group (n=30) existing normal processes were carried out. The data were collected through “The Test for the Assessment of Problem Solving Skills” developed by the researcher. According to the results, it was found out that after the experimental implementations the scores of the students in treatment group-1 regarding the problem solving skills were significantly higher than those of treatment group-2 and control group in terms of “understanding the problem” and “control and assessment” subdimensions. In addition, the scores of the students in treatment group-1 were significantly higher than those of control group with regard to developing a plan, implementing the plan and posing a problem dimensions.